The Acceleration of Ev User in Medan: Through The Implementation of Marketing Mix and Ev Policy - Pasaribu, Widi Sriwahyuni; Aisyah, Chairini; Bahri, Taufik Yuandika (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2025)
Electric Vehicles (EV) are an important pathway for decarbonizing transportation and a form of renewable energy as an environmentally friendly technology to accelerate sustainable development. This is in line with the Indonesian government's target in the Nationally Determined Contribution (NDC) document of reducing emissions by 31.89% in 2030. This paper aims to find out the government policies in accelerating the use of EV in Indonesia, especially in the city of Medan. Semi-structured interviews were done supported by voice note recordings, data collection, and observations of informants who were directly involved in the social conditions studied, that were those from four EV dealers in Medan City and additional informants, who were consumers who already use EV and the community, who have not used an electric vehicle, but know about the existence of the electric vehicle. The result the current policy has resulted in an increase in sales of 50% -60% and the use of EV in the city of Medan by 30%. Policies such as exemption from toll fees, parking in public places, and parking spaces that are easily accessible for electric vehicle drivers are needed. Apart from that, certainty is also needed regarding the policy on entry fees and EV impor taxes, which will affect EV production, especially pricing and variation. In conclusion, the policy cannot stand alone but is supported by a 4P marketing mix strategy (price, product, place, and promotion).Keywords: Electric Vehicle (EV), Marketing Strategy, Policy Incentive, Policy Option